2020
DOI: 10.1002/nag.3052
|View full text |Cite
|
Sign up to set email alerts
|

A calculation method for the embedded depth of stabilizing piles in reinforced slopes

Abstract: Summary Embedded stabilizing piles are a significant optimization measure for traditional piles used to reinforce slopes or landslides. The determination of the embedded depth of the pile top is essential for engineering design. On the basis of the potential overtop‐sliding failure mechanism for a piled slope, the corresponding overall slip surface is assumed to consist of the upper part from the original slip surface of the landslide, and the lower part occurs in the local slide mass upslope of the piles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…At this time, the pile body only bears part of the landslide thrust, and the remaining thrust over the top of the pile is resisted by the rock-soil body itself, so the internal force of the pile body will be much smaller than that of the full-length pile. Studies have shown that this pile structure can effectively overcome the shortcomings of full-length piles [9,10]. Compared with full-length piles, buried piles have shorter force section length, lower maximum bending moment of pile body, and lower material usage, which can reduce costs when treating landslides with larger sliding body thickness, and they have been applied to some extent in landslide treatment in recent years [11].…”
Section: Introductionmentioning
confidence: 99%
“…At this time, the pile body only bears part of the landslide thrust, and the remaining thrust over the top of the pile is resisted by the rock-soil body itself, so the internal force of the pile body will be much smaller than that of the full-length pile. Studies have shown that this pile structure can effectively overcome the shortcomings of full-length piles [9,10]. Compared with full-length piles, buried piles have shorter force section length, lower maximum bending moment of pile body, and lower material usage, which can reduce costs when treating landslides with larger sliding body thickness, and they have been applied to some extent in landslide treatment in recent years [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the strength reduction of the soil in the slip surface and a design factor of safety equal to the calculated stability factor of safety, the horizontal design landslide forces acting on the stabilising piles can be obtained. Xiao (2017) and Yan and Xiao (2020) proposed a TCM based on limit equilibrium theory and a variational calculus method within the framework of limit equilibrium for calculating the earth forces on embedded stabilising piles for reinforced landslides. Furthermore, Ao et al (2020) applied the strength reduction finite element method (SRFEM) to obtain the design landslide forces for embedded stabilising piles and considered the soil-pile friction.…”
Section: Introductionmentioning
confidence: 99%